The microcalcification influence on the ateroma plaque vulnerability - Cilla, M.; Peña, E.; Martínez, M.Á. (Jornada de Jóvenes Investigadores del I3A, 2012)
Rupture of atherosclerotic plaque, which is related to maximal stress conditions in the plaque, isa major cause of mortality worldwide. More careful examination of stress distributions inplaques reveals that it may be caused by the local stress behaviors caused by cap thinning,inflammation, macroscopic heterogeneity, and recently, the presence of microcalcifications, atcritical sites. However, the role of microcalcifications is not yet fully understood and most finiteelement models of blood vessels with atheroma plaque do not consider the heterogeneity of theplaque constituents at the micro-scale. The goal of the present work is to investigate the effectsof microcalcifications on the stress field of an atheroma plaque vessel section. This is achievedby performing a parametric finite element study, assuming a plane strain hypothesis, of anidealized coronary artery cross-section with eccentric atheroma plaque and onemicrocalcification incorporated. The model was extruded at a small length in order to introducesome purely 3D parameters such as the fiber orientation. Healthy (adventitia) and diseased(fibrotic, lipidic and calcification) tissues were considered. The parametric analysis includes themost influential geometric parameter on atheroma vulnerability and the position and dimensionsof the microcalcification: the fibrous cap thickness, the microcalcification ratio, angle andeccentricity. In total, a large set of 108 different geometries were studied. We could concludethat microcalcifications should be considered in the modeling of this kind of problems sincethey cause a significant alteration of the vulnerable risk by increasing the maximum maximalprincipal stress up to 40%.